Meningkatkan Kemampuan Motorik Halus Anak Usia Dini Melalui Kegiatan Menggunting dengan Media Loose Part - Purwani (Bildung: Jurnal Ilmu Pendidikan, 2026)
This study aimed to improve children’s fine motor skills through cutting activities using loose part media in Group B of RA Perwanida Sukorejo Village. The background of this research was based on the low fine motor skill abilities of children in cutting activities, as indicated by poor hand-eye coordination and low interest in the learning media used. This study employed Classroom Action Research (CAR) conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were 20 children of Group B at RA Perwanida Sukorejo in the 2024/2025 academic year. Data collection techniques were carried out through observation and documentation, while data analysis used descriptive qualitative methods and percentage analysis of children’s development. The results showed an improvement in children’s fine motor skills through cutting activities using loose part media. In the pre-cycle stage, there were no children in the very well developed category (0%). In Cycle I, the percentage increased to 20% (4 children), and significantly increased in Cycle II to 65% (13 cildren). In addition, the Undeveloped category, which was 20% in the pre-cycle stage, decreased to 0% in Cycle II. The findings indicate that the use of loose part media can improve children’s fine motor skills, enhance creativity, concentration, hand-eye coordination, and make learning activities more engaging and enjoyable for early childhood learners.